Aspergillosis in domestic and wild birds from Argentina - Della Vedova, Romina (2019)
Aspergillus species are widely distributed throughout the world and are capable of developing parasitic and saprophytic ways of life, allowing Aspergillus to infect living hosts, including plants, insects, birds and mammals. The most common form of aspergillosis in poultry and other birds are respiratory infections. Clinical manifestations depend on the infective dose, pre-existing diseases, and the immune response of the host. The aim of the present manuscript was to study aspergillosis in domestic and wild birds from Argentina. We carried out morphological and molecular identification, and also the determination of susceptibility testing against seven antifungal drugs was conducted. Six birds belonging to different cities of Buenos Aires Province of Argentina were studied. Three of the samples belonged to baby broilers, while the other three samples belonged to an eagle, a pheasant, and a kelp gull. Two isolates were identified as Aspergillus fumigatus by morphological characteristics and growth at 50 ºC. Morphology and BenA sequencing enabled us to identify three isolates as Aspergillus flavus, and one as Aspergillus sydowii. All antifungal drugs tested showed low MIC values, ranging from 0.008 to 1 mg/l. Aspergillosis in birds cause high economical losses and could be controlled by sanitation, avoidance of mouldy food and nest and litter and reducing stress factors.